Concept of research of the wear resistance of metal parts, nitrided in glow discharge with independent parameters. - Пастух, І.М.; Соколова, Г.М. (Problems of Tribology, 2015)
Pastukh I.M., Sokolova G.M. Concept of research of the wear resistance of metal parts, nitrided in glow dis-charge with independent parameters. On the basis of impact complex the model of the study of the wear resistance of metal parts, nitrided in a glow dis-charge with the autonomous (independent) parameters of technological regime was generated. The structure of the relation-ship of factors and components of the model can be the basis for automating of the process of the wear resistance of metal parts controlled formation.